Self-care profiles and patient management of haemodialysis treatments: a descriptive cross-sectional study - Ana Amorim Evaristo; Paulo Marques (Associação de Enfermagem Oncológica Portuguesa, 2018)
This study aimed to explore the self-care theory proposed by Orem and to perform a detailed categorization of the related profiles. The performed research enabled the identification of four profiles and goals were set to establish a correlation between self-care profiles and self-management of the therapeutic regimen; to establish a relationship between demographic characteristics and self-care profiles and to establish a correlation between self-care profiles and obstacles to an effective management of the therapeutic regimen. The design was cross-sectional, descriptive and correlational. Interviews were conducted with 122 patients undergoing haemodialysis in a healthcare unit. Clinical outcomes were extracted from medical records. The results show that patients with the highest scores in the responsible self-care profile are those with improved knowledge (liquid - R=.250; p=.006; medication - R=.246; p=.006); who take better care of their vascular access (R=.186; p=.042); who manage their diet better (R=.247; p=.006); and who face fewer obstacles than the others (R=-.207; p=.022). The research findings show that the implementation of successful nursing treatment plans depends on the knowledge and understanding of patients perceptions regarding self-care and that this indicator will be of the utmost importance when helping patients in the transition to a new health condition and to experience a better quality of life.